Electric Power Analysis and System Optimization of Micro-Hydro Power Plants at the Sentool Plantation, Jember - Irvan Siswanto; Artoto Arkundato; Lutfi Rohman; Bowo Eko Cahyono (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2023)
Sentool Plantation is a plantation area, agro-industrial and agro-tourism are located in Suci Village, Panti District, Jember Regency. This area is at the foot of Mount Argopuro with abundant water sources. In this area there is a river flow that can be utilized as a micro-hydro power plant (PLTMH). PLTMH is a relatively easy power plant to make and apply in rural areas or villages. PLTMH was chosen as an alternative energy source with the principle of developing renewable energy Therefore, in this community service activity want to effort to analyze potency of electric power generation and optimization of the MHP System at the Sentool Plantation which is useful as a consideration PLTMH development to meet the electricity needs of the local community and electricity needs for the development of agro-tourism. Power potential analysis process and optimization of the PLTMH system is carried out with two stages of data analysis, namely the calculation of the potential power theoretical and simulation using HOMER Energy software. HOMER Energy is used for profit simulation. The greatest potency generated power is 53.12 kWh with a discharge of 0.398 m3/s and the smallest is 18.05 kWh with a discharge of 0.135 m3/s. Simulations using HOMER Energy software produce system configurations PLTMH with an estimated capital cost of IDR 48,600,000, operational costs and maintenance 42,900,000 per year, NPC of IDR -2,557,215,000, LCoE of IDR-573.63. PLTMH has a capacity of 37.1 kW with annual production of 290,573 kW, get a profit of IDR 212,747,987.50 from the sale of energy. The results of the calculation of the water discharge, the height of the water fall and the generated power are quite high, the water flow in the Sentool Plantation is technically feasible to build a micro-hydro power plant (PLTMH).